Effects of Feed Additive Raafres AQ on Feeding, Growth, Tissue Indices and Leucocytes Count in Carp Juveniles - James, R; Sampath, K (Fishery Technology, 2025)
Effect of different levels (0, 2.5, 5, 7.5 and 10%) of feed additive raafres AQ on feed intake, growth, tissue indices and leucocytes count was studied in the carps Cirrhinus mrigala and Labeo rohita for a period of 28 days. The experimental diets were prepared with 35% basal diet of protein. The dietary administration of 5 and 7.5% raafres AQ elicited the maximum growth, tissue indices and protein efficiency ratio (PER) with low feed conversion ratio (FCR) in C. mrigala and L. rohita respectively. However, the higher doses of raafres AQ (7.5 – 10% in C. mrigala and 10% in L. rohita) reduced the above parameters. It suggests that lower doses of raafres AQ have anabolic effect stimulating feed intake, growth, tissue indices and PER and catabolic effect at higher doses causing reduction of the above parameters in chosen carps. As C. mrigala fed with 5% and L. rohita with 7.5% raafres AQ showed highest number of leucocytes, lymphocytes, neutrophil and monocytes; these are considered as optimum doses. L. rohita required a higher dose of raafres AQ compared to C. mrigala.